2017
DOI: 10.1259/bjr.20160829
|View full text |Cite|
|
Sign up to set email alerts
|

Dose specification for hippocampal sparing whole brain radiotherapy (HS WBRT): considerations from the UK HIPPO trial QA programme

Abstract: Objective: The HIPPO trial is a UK randomized Phase II trial of hippocampal sparing (HS) vs conventional wholebrain radiotherapy after surgical resection or radiosurgery in patients with favourable prognosis with 1-4 brain metastases. Each participating centre completed a planning benchmark case as part of the dedicated radiotherapy trials quality assurance programme (RTQA), promoting the safe and effective delivery of HS intensity-modulated radiotherapy (IMRT) in a multicentre trial setting. Methods: Submitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Normal brain volumes were defined as whole brain volume with the subtraction of the GTV. Dose constraints followed the general constraints presented in Supplement Table 1 [28][29][30], and in particular, we constrained V24.4 to be less than 10 cm 3 of normal brain to limit the predicted risk of radionecrosis to 5% for fivefraction radiation [31]. We considered dose constraints on all OARs prior to the dose on PTVs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Normal brain volumes were defined as whole brain volume with the subtraction of the GTV. Dose constraints followed the general constraints presented in Supplement Table 1 [28][29][30], and in particular, we constrained V24.4 to be less than 10 cm 3 of normal brain to limit the predicted risk of radionecrosis to 5% for fivefraction radiation [31]. We considered dose constraints on all OARs prior to the dose on PTVs.…”
Section: Methodsmentioning
confidence: 99%
“…All HS-WBRT plans were planned using VMAT based on a monoisocentric technique with two coplanar 360°-arcs of Truebeam Linac 6MV flattened beam. Hippocampal avoidance regions were developed with a geometrical isotropic expansion of 5 mm to the hippocampus [29,30] unless there was a lesion within 5 mm of a hippocampus, in which case we only spared the contralateral hippocampus. We prescribed 20 Gy in 5 fractions to the whole brain with 3 mm expansion, sparing the hippocampal avoidance regions (Fig.…”
Section: Hs-wbrtmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of D w,m * can also be helpful in multi-centre activities, such as clinical trials, audits, benchmarking, and shared models for automation. In these environments, several dose reporting modes can coexist and consistency is crucial for the significance and robustness of the results (Megias et al 2017, Palmer et al 2017, Lehmann et al 2018, Lee et al 2019, Panettieri et al 2019. Sometimes, one dose quantity is imposed on all centres, but this is not the case in most situations.…”
Section: Other Potential Applicationsmentioning
confidence: 99%
“…HIPPO hypothesized that irradiation of the bilateral hippocampi may cause part of the adverse neurocognitive effect from WBRT, and reducing dosage to the hippocampi may help preserve NCF. 8 HA-WBRT may delay onset, or reduce severity of NCF decline without decreased intracranial disease control, therefore it improves outcome of the patients. 9 Previous studies revealed that cells of the hippocampus were highly sensitive to radiation even at low doses.…”
Section: Introductionmentioning
confidence: 99%